Relational Aggression vs. Well-Being: Uncovering the Impact of Relational Harm Among Adolescents - Normalasari, Cahya; Biju Thomas, Smita; Nazri Abdul Rahman , Mohd; Syahputra, Yuda (Asosiasi Asesmen Pendidikan (AAP), 2025)
The purpose of this study was to investigate relational aggression if any, the detrimental consequences of relational aggression for eighth-grade students’ psychological well-being at one of the junior high schools in Jakarta. The present research utilized a quantitative correlational research design involving 150 students, randomly selected. Data were collected through questionnaires and analyzed using simple regression with IBM SPSS version 20. The research report showed a significance value of .000 (p < .005); with a t value of –10.054 indicating relational aggression had a significant negative impact on the students’ psychological well-being. The negative t-value indicates an inverse correlation between relational aggression the students’ psychological well-being; the higher the relational aggression the less psychological well-being students exhibited on the measure. The R Square value of 0.406 indicates that relational aggression accounted for 40.6% in the variance for psychological well-being. While the remaining variance of 59.4% would be indicating variables not previously assessed in this study. The model provides a suitable account to predict psychological well-being. Relational aggression must be taken into consideration if we expect to promote positive mental health for students.